Sarcoma histiocítico: análise molecular pela técnica de hibridação genômica comparativa, microRNA e imunoistoquímica - Herbst, Thiago Eugenio Gouveia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Histiocytic sarcoma (HS) is a malignant neoplasm characterized by the proliferation of large cells that have morphological and immunophenotypic features similar to mature tissue histiocytes. It is a rare neoplasm, accounting for less than 1% of non-Hodgkin lymphomas. This rarity is partly explained by the difficulties in its diagnostic and morphological characterization, since it is confused with other pleomorphic malignant neoplasms. The objectives of this study were to evaluate changes in genomic gains and losses using the comparative genomic hybridization technique (CGH-array), microRNA profile (miRNA) evaluation, determine the principal morphological criteria and immunohistochemical markers (IMH) that could define this entity, and identify entities that can mistakenly lead to underdiagnosis. To achieve this, 7,600 pathology reports were reviewed and, of these, 47 possible cases of HS with nodal presentation were selected. Four cases with an established diagnosis of HS were also included in the analysis. Twelve morphological criteria and 5 IMH markers were evaluated. Among the 47 cases, 7 cases of HS were identified that had initially been diagnosed as undifferentiated metastatic neoplasm (undifferentiated carcinoma) or metastatic melanoma. The IMH markers that were most efficient for complementary diagnosis were CD163 and CD68. Evaluation of the profiles of 377 miRNAs showed clustering of 51 miRNA compared with the control; 44 were hypoexpressed and 7 were hyperexpressed and the most relevant were: miR-486-5p, miR-92a, miR-15b-5p (hyporegulated); and miR-10b-5p, miR-455-5p and miR-19 (hyperexpressed). These miRNA are involved in apoptosis, cell growth and proliferation pathways. The main genes involved in pathogenesis and candidates for validation in future studies are: ERBB2, TGFB1, TNF (activated); and TP53 and PD98059 (inhibited). These genes may represent future therapeutic targets. The CGH-array proved to be unfeasible in ...

O Sarcoma Histiocítico (SH) é uma neoplasia maligna caracterizada pela proliferação de células grandes que possuem aspecto morfológico e imunofenotípico semelhantes ao histiócito maduro tecidual. É uma neoplasia rara, perfazendo menos que 1% dos Linfomas Não-Hodgkin. Tal raridade pode ser explicada pela dificuldade de sua caracterização diagnóstica e morfológica, confundindo-se com outras neoplasias malignas pleomórficas. Os objetivos do presente estudo são: avaliar alterações no padrão de ganhos e perdas genômicas pela técnica de Hibridação Genômica Comparativa (CGH-array), avaliação do perfil de MicroRNA (miRNA), apontar os principais critérios morfológicos e marcadores imunoistoquímicos (IMH) que venham a definir esta entidade e identificar quais entidades que erroneamente podem levar a subdiagnostico.Para tanto, foram revisados 7.600 laudos anatomopatológicos e, destes, foram selecionados 47 casos possíveis de SH, com apresentação nodal. Somando-se a estes, quatro casos sabidamente com diagnóstico de SH foram incluídos na análise. Foram avaliados 12 critérios morfológicos e 05 marcadores IMH. Dos 47 casos, foram localizados 07 SH, cujo diagnóstico inicial foi de neoplasia indiferenciada metastática (carcinoma indiferenciado) ou melanoma metastático. Os marcadores IMH que se mostraram mais eficientes para complementação diagnóstica foram CD163 e CD68. A avaliação do perfil de 377 miRNAs demonstrou clusterização de 51 miRNA, quando comparado ao controle, sendo 44 hipoexpresssos e 07 hiperexpressos, sendo os mais relevantes: miR-10b-5p, miR-455-5p e miR-19 (hiperexpressos); miR-486-5p, miR-92a, miR-15b-5p (hiporegulados). Tais miRNA estão envolvidos nas vias da apoptose, crescimento e proliferação celular. Os principais genes envolvidos na patogenia e candidatos a validação com futuros estudos são: ERBB2, TGFB1,TNF(ativados) e TP53 e PD98059 (inibidos).Tais genes podem corresponder a futuros...
Keywords: Sarcoma histiocítico; Linfoma; Imunohistoquímica; Expressão gênica; Morfologia; Lymphomas